Analisis pengaruh laba akuntansi dan arus kas terhadap dividen kas (Studi empiris pada perusahaan industri barang konsumsi yang terdaftar di BEI) - Satriawan, Raja Adri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The aim of this research is to investigate the effect of the accounting earnings and cash flow on dividend cash.The sample in this research is consumer goods companies which are listed in Indonesia Stock Exchange in the period of 2007-2012. Totally, there are 15 listed companies which are selected using purposive sampling method.To analyze data, this research employs multiple regression analysis. The results of this research indicate that accounting earnings has significant effect on cash dividend. In contrast, cash flow has no significant effect on dividend cash.Based on the results of the calculations can be seen that the coefficient of determination R square value obtained was 66.4%. The figure gives the sense that the dividend cash changes are affected by the accounting earnings and cash flows for the remaining 66.4% and 33.6% influenced by other factors.Keywords: Dividend cash, Accounting Earnings, and Cash flow